2014
DOI: 10.3390/ijerph110504991
|View full text |Cite
|
Sign up to set email alerts
|

Mental and Behavioral Disorders Due to Substance Abuse and Perinatal Outcomes: A Study Based on Linked Population Data in New South Wales, Australia

Abstract: Background: The effects of mental and behavioral disorders (MBD) due to substance use during peri-conception and pregnancy on perinatal outcomes are unclear. The adverse perinatal outcomes of primiparous mothers admitted to hospital with MBD due to substance use before and/or during pregnancy were investigated. Method: This study linked birth and hospital records in NSW, Australia. Subjects included primiparous mothers admitted to hospital for MBD due to use of alcohol, opioids or cannabinoids during peri-conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 25 publications
3
23
0
3
Order By: Relevance
“…Preterm birth refers to birth that occurs less than 37 weeks of gestation . Sixteen studies mentioned an association between substances use during pregnancy and preterm birth . The association was found significant with most of the drugs included in the studies (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Preterm birth refers to birth that occurs less than 37 weeks of gestation . Sixteen studies mentioned an association between substances use during pregnancy and preterm birth . The association was found significant with most of the drugs included in the studies (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…This refers to neonate weight of less than 2500 g at birth . Nine studies reported that the exposure of newborn infants to single or polysubstance use in pregnancy increased the possibility of low birthweight (Table ) . The use of cannabis, opiate or heavy alcohol consumption was significantly associated with low birthweight .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations